IMPLEMENTASI KHAZANAH SURAU TERHADAP PENDIDIKAN ISLAM MODERN - Alfurqan, Alfurqan; Zein, Zainurni; Salam, Abdul (Universitas Pendidikan Indonesia, 2019)
Abstract. This research is motivated by looking at the contribution of the mosque to modern Islamic education. Surau is the first Islamic educational institution that is present in Minangkabau. In addition to Islamic education, surau also teaches traditional knowledge and martial arts in the form of silat. But over time and the development of times and technology, the existence of surau began to erode with the advent of Modern Islamic education such as Thawalib, Adabiyah and so forth in the early 20th century. Even, the madrasa on the basis of surau have also changed from the halaqah system to the classical system. Through this research, researchers want to know the extent of these changes. Are the values of surau education still applied in modern Islamic education ?. This research uses the field reaserch method with a qualitative descriptive approach. From this study, it was concluded that the values of surau education were still implemented in modern Islamic education namely madrasa and pesantren. This can be seen from the references used by madrassas and pesantren which are not much different from the references used in the surau educational institution.Abstrak. Penelitian ini dilatar belakangi dengan melihat kontribusi surau terhadap pendidikan Islam modern. Surau merupakan lembaga pendidikan Islam pertama yang hadir di Minangkabau. Selain pendidikan Islam, surau juga mengajarkan pengetahuan adat dan beladiri berupa silat. Namun seiring berjalannya waktu dan perkembangan zaman dan teknologi, eksistensi surau mulai terkikis dengan munculnya pendidikan Islam Modern seperti Thawalib, Adabiyah, dan lain sebagainya pada awala abad ke-20. Bahkan madrasah dengan basis surau juga ikut berubah dari sistem halaqah kepada sistem klasikal. Melalui penelitian ini, peneliti ingin mengetahui sejauhmana perubahan ini terjadi. Apakah nilai-nilai pendidikan surau masih diterapkan dalam pendidikan Islam modern?. Penelitian ini menggunakan metode field reaserch (studi lapangan) dengan pendekatan deskriptif kualitatif. Dari penelitian ini, disimpulkan bahwa nilai-nilai pendidikan surau masih terimplementasikan dalam pendidikan Islam modern yakni madrasah dan pesantren. Hal ini dapat dilihat dari referensi-referensi yang digunakan oleh madrasah dan pesantren yang tidak jauh berbeda dari referensi yang digunakan pada lembaga pendidikan surau.